Marketing Public Relations dalam Membangun Brand Awareness - Aliyah Salma Dwi Pratiwi; Maman Suherman (Bandung Conference Series: Public Relations, 2023)
Abstract. The development of technology in this era dramatically affects the lives of Indonesian people, one of which is the ease in the field of information dissemination. The success of antidote.reseau as one of the UMKM in the fashion industry in marketing its products has attracted the interest of researchers to explore Marketing Public Relations activities which are used in the hope that it will have a good impact on other UMKM. Three issues are discussed in this study, namely: (1) the Management of Instagram @antidote.reseau in conveying information to the public; (2) The intensity of information delivery by the antidote.reseau through Instagram in increasing public knowledge about the brand; (3) The reasons for the antidote.reseau using Instagram to build brand awareness. In examining these three issues, researchers used a case study research method with a qualitative approach. The author uses a conceptual framework in the form of theories and concepts as an analytical knife in answering the problem formulation that has been determined. Theories and concepts used by the author are Marketing Public Relations theory, Public Relations theory, brand awareness theory, new media theory, and the Instagram concept. Abstrak. Dengan berkembangnya teknologi pada zaman ini sangat mempengaruhi kehidupan masyarakat Indonesia, salah satunya adalah kemudahan di bidang penyebaran informasi. Keberhasilan Antidote Reseu sebagai salah satu UMKM di bidang industri Fashion dalam memasarkan produknya menarik minat peneliti untuk mendalami kegiatan Marketing Public Relation yang digunakan dengan harapan dapat memberikan dampak baik bagi UMKM lainnya. Terdapat tiga permasalahan yang dibahas dalam penelitian ini, yakni tentang : (1) Pengelolaan Instagram @antidote.reseau dalam menyampaikan informasi kepada publik; (2) Intensitas penyampaian informasi oleh antidote.reseau melalui Instagram dalam meningkatkan pengetahuan khalayak tentang brand; (3) Alasan antidote.reseau menggunakan Instagram dalam membangun brand awareness. Dalam meneliti terhadap tiga persoalan tersebut, peneliti menggunakan metode penelitian studi kasus dengan pendekatan kualitatif. Penggunaan kerangka konseptual berupa teori dan konsep digunakan sebagai pisau analisis oleh penulis dalam menjawab rumusan masalah yang telah ditentukan. Teori dan konsep yang digunakan penulis yaitu teori Marketing Public Relations, teori Public Relations, teori brand awareness, teori new media dan konsep Instagram.